Electrolytic capacitors

The electrolytic capacitor design with a conductive polymer layer and controlled electrolyte moisture content addresses the challenge of high capacity and low ESR, ensuring stable performance by enhancing adhesion and reducing leakage current.

JP7611538B2Active Publication Date: 2025-01-10PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023156119
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2015-04-28
Filing Date
2023-09-21
Publication Date
2025-01-10
Estimated Expiration
2036-03-10

AI Technical Summary

Technical Problem

Existing electrolytic capacitors face challenges in achieving high capacity while maintaining low equivalent series resistance (ESR) and preventing increases in leakage current, particularly due to insufficient adhesion of the carbon-containing layer and moisture-related issues in the electrolyte.

Method used

The capacitor design includes an anode foil with a dielectric layer, a cathode foil with a conductive carbon layer, and a conductive polymer layer interposed between them, using a solvent with a boiling point of 180°C or higher and controlling the electrolyte's water content between 0.1% to 6.0% by mass to enhance adhesion and reduce ESR.

Benefits of technology

This configuration ensures high capacity and reduces leakage current while suppressing ESR, maintaining performance over time by improving adhesion and stability of the capacitor elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611538000002
    Figure 0007611538000002
  • Figure 0007611538000003
    Figure 0007611538000003
  • Figure 0007611538000001
    Figure 0007611538000001
Patent Text Reader

Abstract

To provide an electrolytic capacitor using an electrolyte, the electrolytic capacitor attaining a high capacity and also suppressing increase of an ESR and reducing leakage of a current at the same time.SOLUTION: The electrolytic capacitor includes a capacitor element and an electrolyte solution. The capacitor element includes: an anode foil including a dielectric layer; a negative foil facing the positive foil, the negative foil having a layer containing conductive carbon in the surface; and a conductive polymer layer located between the anode foil and the cathod foil, the conductive polymer layer containing a conductive polymer. The electrolyte liquid includes a first solvent. The first solvent does not have a boiling point or a boiling point of at least 180°C. The conductive polymer layer is formed by using a diffusion body or a solution containing the conductive polymer. The electrolyte contains water in a concentration of 0.1-6.0 mass%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrolytic capacitor including a capacitor element having a conductive polymer layer and an electrolyte. [Background technology]

[0002] Electrolytic capacitors having an anode body with a dielectric layer and a conductive polymer layer formed so as to cover at least a portion of the dielectric layer are considered to be promising as small-sized, large-capacity, low-ESR capacitors.

[0003] Patent Document 1 proposes an electrolytic capacitor in which an electrolytic solution is impregnated into a capacitor element including an anode foil having a dielectric layer formed thereon, a cathode foil, a separator interposed between the anode foil and the cathode foil, and a conductive polymer layer formed on the surfaces of the dielectric layer, the separator, and the cathode foil.

[0004] Patent Document 2 proposes forming an intervening layer containing aluminum carbide between aluminum and a carbon-containing layer formed on the surface of the aluminum in the cathode of a solid electrolytic capacitor in order to improve adhesion. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-010657 A [Patent Document 2] JP 2006-100478 A Summary of the Invention [Problem to be solved by the invention]

[0006] In the solid electrolytic capacitor of Patent Document 2, a carbon-containing layer is provided on the cathode in order to increase the capacity, and it is expected that the ESR will be reduced by improving the conductivity of the cathode. In addition, in an electrolytic capacitor using an electrolytic solution as in Patent Document 1, defects in the dielectric layer formed on the anode are easily repaired, so that an increase in leakage current and a decrease in withstand voltage can be suppressed. However, in reality, even if a capacitor element having a carbon-containing layer formed on the cathode is combined with an electrolytic solution, there are cases where sufficient repairability is not obtained, and it is difficult to ensure sufficient adhesion of the carbon-containing layer, which may result in an increase in ESR.

[0007] An object of the present invention is to ensure high capacitance and reduce leakage current while suppressing an increase in ESR in an electrolytic capacitor that uses an electrolyte. [Means for solving the problem]

[0008] One aspect of the present invention provides a capacitor comprising a capacitor element and an electrolyte, The capacitor element is an anode foil having a dielectric layer formed thereon; a cathode foil facing the anode foil and having a layer containing conductive carbon formed on a surface thereof; a conductive polymer layer interposed between the anode foil and the cathode foil and including a conductive polymer; The electrolyte solution includes a first solvent, The first solvent has no boiling point or has a boiling point of 180° C. or higher; the conductive polymer layer is formed using a dispersion or a solution containing the conductive polymer, The electrolytic capacitor has a water content of 0.1 to 6.0% by mass of the electrolytic solution. This specification discloses the following examples as other examples of electrolytic capacitors. [Example 1] The capacitor element and the electrolyte are provided. The capacitor element is an anode foil having a dielectric layer formed thereon; a cathode foil facing the anode foil and having a conductive layer formed thereon, the conductive layer including a carbon layer containing conductive carbon; a conductive polymer layer interposed between the anode foil and the cathode foil and including a conductive polymer; the conductive polymer layer is formed using a dispersion or a solution containing the conductive polymer, The electrolytic capacitor, wherein the water content of the electrolytic solution is 0.1 to 6.0% by mass. [Example 2] The electrolytic capacitor of Example 1, wherein the carbon layer is a deposited film of the conductive carbon. [Example 3] The electrolytic capacitor according to Example 1 or 2, wherein the electrolyte solution includes a first solvent that has no boiling point or a boiling point of 180° C. or higher. [Example 4] 4. The electrolytic capacitor of Example 3, wherein the first solvent comprises a polyol. [Example 5] The electrolytic capacitor according to Example 3 or 4, wherein the amount of the first solvent contained in the electrolytic solution is 3 to 90 mass %. Effect of the Invention

[0009] According to the above aspects of the present invention, in an electrolytic capacitor using an electrolyte, it is possible to ensure a high capacity, suppress an increase in ESR, and reduce leakage current. [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic cross-sectional view of an electrolytic capacitor according to one embodiment of the present invention. [Diagram 2] 2 is a schematic diagram for explaining the configuration of a capacitor element in the electrolytic capacitor of FIG. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the electrolytic capacitor of the present invention will be described with reference to the drawings as appropriate. However, the present invention is not limited to the following embodiments. <Electrolytic capacitor> Fig. 1 is a schematic cross-sectional view of an electrolytic capacitor according to one embodiment of the present invention, and Fig. 2 is a schematic exploded view of a portion of a capacitor element included in the electrolytic capacitor.

[0012] 1, the electrolytic capacitor includes a capacitor element 10 and is housed in an exterior case (specifically, a bottomed case 11) together with an electrolyte (not shown). The exterior case includes bottomed case 11 that houses capacitor element 10 therein, an insulating sealing member 12 that closes the opening of bottomed case 11, and a seat plate 13 that covers sealing member 12. The vicinity of the open end of bottomed case 11 is drawn inward, and the open end is curled so as to be crimped to sealing member 12.

[0013] As shown in Fig. 2, capacitor element 10 includes anode foil 21 connected to lead tab 15A, cathode foil 22 connected to lead tab 15B, and separator 23. Anode foil 21 and cathode foil 22 are wound with separator 23 interposed therebetween. The wound anode foil, cathode foil, and separator are also called a wound body. The outermost periphery of capacitor element 10 is fixed with a stop tape 24. Note that Fig. 2 shows a partially unfolded state of capacitor element 10 before the outermost periphery is fixed.

[0014] In the capacitor element 10, the anode foil 21 is a metal foil whose surface is roughened to have irregularities, and a dielectric layer is formed on the metal foil having irregularities. The cathode foil 22 facing the anode foil 21 is a metal foil, and a conductive layer is formed on the metal foil. The conductive layer formed on the cathode foil 22 includes a carbon layer containing conductive carbon. A conductive polymer is attached to at least a part of the surface of the dielectric layer on the anode foil 21 and at least a part of the surface of the conductive layer on the cathode foil 22 to form a conductive polymer layer. The conductive polymer may be attached to any position between the anode foil 21 and the cathode foil 22. For example, the conductive polymer may cover at least a part of the surface of the dielectric layer formed on the anode foil 21 and at least a part of the surface of the conductive layer on the cathode foil 22, and may further cover at least a part of the surface of the separator 23. In this way, a conductive polymer layer is interposed between the anode foil 21 and the cathode foil 22.

[0015] In electrolytic capacitors, the conductive polymer (specifically, a coating containing a conductive polymer) that covers at least a portion of the surface of the anode foil, cathode foil, separator, etc. is generally referred to as a solid electrolyte layer (or conductive polymer layer).

[0016] The configuration of the electrolytic capacitor according to the embodiment of the present invention will be described in more detail below.

[0017] The capacitor element includes an anode foil having a dielectric layer formed thereon, a cathode foil having a conductive layer formed thereon, and a conductive polymer layer interposed between the anode foil and the cathode foil, and may further include a separator as necessary. (Capacitor element) (anode foil) The anode foil may be, for example, a metal foil having a roughened surface. The type of metal constituting the metal foil is not particularly limited, but it is preferable to use a valve metal such as aluminum, tantalum, or niobium, or an alloy containing a valve metal, in terms of ease of forming a dielectric layer.

[0018] The metal foil surface can be roughened by a known method. By roughening, a plurality of projections and recesses are formed on the surface of the metal foil. The roughening is preferably performed, for example, by etching the metal foil. The etching may be performed, for example, by DC electrolysis or AC electrolysis.

[0019] (Dielectric layer) The dielectric layer is formed on the surface of the anode foil. Specifically, since the dielectric layer is formed on the surface of the roughened metal foil, the dielectric layer is formed along the inner wall surfaces of the holes and depressions (pits) on the surface of the anode foil.

[0020] The method for forming the dielectric layer is not particularly limited, but the dielectric layer can be formed by subjecting a metal foil to a chemical conversion treatment. The chemical conversion treatment may be performed, for example, by immersing the metal foil in a chemical conversion solution such as an ammonium adipate solution. In the chemical conversion treatment, a voltage may be applied to the metal foil while it is immersed in the chemical conversion solution, if necessary.

[0021] Usually, from the viewpoint of mass production, a metal foil made of a large valve metal or the like is subjected to a surface roughening treatment and a chemical conversion treatment. In this case, the treated foil is cut to a desired size to prepare an anode foil 21 having a dielectric layer formed thereon.

[0022] (cathode foil) Like the anode foil, a metal foil is used for the cathode foil 22. There are no particular limitations on the type of metal, but it is preferable to use a valve metal such as aluminum, tantalum, or niobium, or an alloy containing a valve metal.

[0023] When a conductive polymer layer is formed on the surface of the cathode foil using a dispersion or solution containing a conductive polymer, a conductive polymer layer with high uniformity and flexibility can be obtained.

[0024] (Conductive layer) The conductive layer as a whole is desirably formed of an inorganic material (such as a metal, a metal compound, and / or conductive carbon) having electrical conductivity, and is distinguished from a conductive polymer layer formed of an organic material. Since the conductive layer as a whole is formed of an inorganic material, it can also be called an inorganic conductive layer. The conductive layer includes at least a carbon layer in contact with the conductive polymer layer.

[0025] The carbon layer contains conductive carbon. Examples of conductive carbon include amorphous carbon, carbon black such as acetylene black, soft carbon, hard carbon, graphite, and carbon fibers such as carbon nanotubes. The carbon layer may contain one type of conductive carbon or two or more types of conductive carbon.

[0026] The carbon layer may be a layer containing conductive carbon and a binder, but it is preferable that the proportion of conductive carbon is as high as possible. The amount of conductive carbon in the carbon layer is preferably, for example, 95 mass % or more or 99 mass % or more. The carbon layer may be formed by forming a layer containing conductive carbon and a binder and removing the binder by heat treatment. In particular, the carbon layer is preferably a layer made of conductive carbon. Among them, it is preferable that the carbon layer is a deposited film of conductive carbon (particularly, amorphous carbon).

[0027] The conductive layer may include only a carbon layer, or may further include a conductive base layer from the viewpoint of enhancing adhesion. The base layer is formed on the surface of the cathode foil, and the carbon layer can be formed on the base layer. When the conductive layer includes a base layer, the carbon layer may be formed directly on the surface of the base layer, or may be formed on the base layer with another conductive layer interposed between the carbon layer and the base layer.

[0028] The base layer constituting a part of the conductive layer includes a non-carbonaceous conductive inorganic material such as a metal or a conductive metal compound. Examples of the metal include titanium and / or nickel. The metal compound is preferably a metal nitride such as titanium nitride.

[0029] As in Patent Document 2, when the conductive layer formed on the cathode foil contains a carbide component such as aluminum carbide (aluminum carbide, etc.), the life characteristics may be reduced. For example, conductive aluminum carbide reacts with moisture in the electrolytic capacitor (particularly in the electrolyte) to generate methane and insulating aluminum hydroxide, of which the insulating aluminum hydroxide is present between the cathode foil and the conductive polymer layer. As a result, when charging and discharging are repeated, it becomes difficult to ensure electrical connection between the cathode foil and the conductive polymer layer. Therefore, from the viewpoint of improving the life characteristics, it is preferable that the conductive layer does not substantially contain a carbide component (aluminum carbide, etc.). The amount of the carbide component (aluminum carbide, etc.) in the conductive layer is preferably 1 mass % or less.

[0030] The conductive layer has a thickness of, for example, 1 nm to 10 μm. When the carbon layer is a deposited film, the conductive layer may have a thickness of, for example, 1 nm to 100 nm, and when the carbon layer is formed from a layer containing a conductive inorganic material and a binder, the conductive layer may have a thickness of, for example, 100 nm to 10 μm. When the conductive layer has a thickness in this range, it is easy to ensure high conductivity and high capacity.

[0031] The thickness of the conductive layer may be an average thickness obtained by averaging thicknesses measured at multiple points (for example, 10 points) in an image of the cross section.

[0032] (Separator) Separator 23 may be made of, for example, a nonwoven fabric containing fibers of cellulose, polyethylene terephthalate, vinylon, or polyamide (for example, aliphatic polyamide, aromatic polyamide such as aramid).

[0033] The capacitor element 10 can be produced by a known method. For example, the capacitor element 10 may be produced by stacking an anode foil 21 having a dielectric layer formed thereon and a cathode foil 22 having a conductive layer formed thereon with a separator 23 interposed therebetween, and then forming a conductive polymer layer between the anode foil 21 and the cathode foil 22. The capacitor element 10 may be produced by winding the anode foil 21 having a dielectric layer formed thereon and the cathode foil 22 having a conductive layer formed thereon with the separator 23 interposed therebetween to form a wound body as shown in FIG. 2, and forming a conductive polymer layer between the anode foil 21 and the cathode foil 22. When forming the wound body, the lead tabs 15A and 15B may be wound while being wound, so that the lead tabs 15A and 15B are planted from the wound body as shown in FIG. 2.

[0034] The material of the lead tabs 15A and 15B is not particularly limited as long as it is a conductive material. The surfaces of the lead tabs 15A and 15B may be subjected to a chemical conversion treatment. Furthermore, the portions of the lead tabs 15A and 15B that contact the sealing member 12 and the portions connected to the lead wires 14A and 14B may be covered with a resin material.

[0035] The material of the lead wires 14A, 14B connected to the lead tabs 15A, 15B, respectively, is not particularly limited, and may be a conductive material or the like.

[0036] Of anode foil 21, cathode foil 22, and separator 23, the one located in the outermost layer of the wound body (cathode foil 22 in FIG. 2) has an edge of the outer surface fixed with stop tape 24. When anode foil 21 is prepared by cutting a large metal foil, a chemical conversion treatment may be further performed on the capacitor element in the wound body, in order to provide a dielectric layer on the cut surface of anode foil 21.

[0037] (Conductive polymer layer) The conductive polymer layer is interposed between the anode foil 21 and the cathode foil 22. The conductive polymer layer is preferably formed on at least a portion of the surface of the dielectric layer formed on the surface of the anode foil 21 so as to cover the dielectric layer, and more preferably formed so as to cover as much of the dielectric layer as possible. The conductive polymer layer is preferably formed on at least a portion of the surface of the conductive layer formed on the surface of the cathode foil 22 so as to cover the conductive layer, and more preferably formed so as to cover as much of the conductive layer as possible. When the capacitor element includes a separator, the conductive polymer layer may be formed not only on the surfaces of the dielectric layer and the conductive layer, but also on the surface of the separator.

[0038] Generally, the conductive polymer layer can be formed by using a dispersion in which fine particles of a conductive polymer are dispersed in a dispersion medium or a solution in which a conductive polymer is dissolved in a solvent, or by polymerizing a conductive polymer precursor (such as a monomer or oligomer that is the raw material for the conductive polymer) in contact with an anode foil and a cathode foil.

[0039] In the latter case, the strong reactivity of the oxidizing agent for the polymerization reaction and the monomer itself corrodes the cathode foil and anode foil, which results in poor contact between the foil and the conductive polymer layer, and between the cathode foil and the conductive layer, resulting in a decrease in capacitance and an increase in ESR. The oxidizing agent and monomer remaining after polymerization cannot be sufficiently removed even by washing, which also has a negative effect on the life of the electrolytic capacitor.

[0040] In the present invention, a conductive polymer layer is formed using a dispersion in which fine particles of a conductive polymer are dispersed in a dispersion medium or a solution in which a conductive polymer is dissolved in a solvent. Such a conductive polymer layer is formed by contacting the dispersion or solution with the anode foil and the cathode foil, so that the conductive polymer adheres to the periphery of the anode foil and the cathode foil. By using such a conductive polymer layer, corrosion of the cathode foil and the anode foil is suppressed, and contact between the conductive layer of the anode foil and the cathode foil and the conductive polymer layer, and between the cathode foil and the conductive layer can be ensured. Therefore, an increase in ESR can be suppressed, and a high capacity can be easily ensured.

[0041] (conductive polymer) Examples of the conductive polymer contained in the conductive polymer layer include polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylenevinylene, polyacene, polythiophenevinylene, etc. These may be used alone or in combination of two or more kinds, or may be copolymers of two or more kinds of monomers.

[0042] In this specification, polypyrrole, polythiophene, polyfuran, polyaniline, etc. refer to polymers having polypyrrole, polythiophene, polyfuran, polyaniline, etc. as their basic skeletons, respectively. Therefore, polypyrrole, polythiophene, polyfuran, polyaniline, etc. may also include their respective derivatives. For example, polythiophene includes poly(3,4-ethylenedioxythiophene), etc.

[0043] The conductive polymer may be used alone or in combination of two or more kinds.

[0044] The weight average molecular weight of the conductive polymer is not particularly limited, but is, for example, 1,000 to 1,000,000.

[0045] (Dopant) The conductive polymer layer may contain a dopant. The dopant may be contained in the conductive polymer layer in a state where it is doped into the conductive polymer, or may be contained in the conductive polymer layer in a state where it is bonded to the conductive polymer.

[0046] As the dopant, a polyanion can be used. Specific examples of the polyanion include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid, polymethacryl sulfonic acid, poly(2-acrylamido-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, and polyacrylic acid. Among them, polyanions derived from polystyrene sulfonic acid are preferred. These may be used alone or in combination of two or more. These may also be polymers of a single monomer or copolymers of two or more monomers.

[0047] The weight-average molecular weight of the polyanion is not particularly limited, but is, for example, 1,000 to 1,000,000. A conductive polymer containing such a polyanion is likely to be uniformly dispersed in a solvent, and is likely to be uniformly attached to the surfaces of the dielectric layer and conductive layer.

[0048] (electrolyte) In solid electrolytic capacitors, it is expected that the use of an electrolyte will increase the repairability of the dielectric layer and suppress leakage current. However, when a carbon layer and an electrolyte are actually combined, the repairability of the dielectric layer may not be sufficient.

[0049] However, in practice, when a cathode foil having a conductive layer including a carbon layer is combined with an electrolyte, the moisture content of the electrolyte can be set to 0.1 mass % or more to obtain a repair effect on the dielectric layer, thereby reducing leakage current.

[0050] On the other hand, when the electrolyte contains moisture, the capacitance decreases and the ESR increases as the electrolytic capacitor is used for a certain period of time. This is believed to be due to the moisture in the electrolyte reducing the adhesion between the cathode foil and the conductive layer including the carbon layer. In addition, when an electrolyte containing moisture is used and the conductive polymer layer is formed by polymerizing a conductive polymer precursor in contact with the cathode foil, the remaining oxidizing agent and precursor become active due to the action of moisture in the electrolyte, causing corrosion of the foil and reducing the adhesion between the cathode foil and the conductive layer, and between the anode foil or the conductive layer and the conductive polymer layer.

[0051] In this embodiment, the conductive polymer layer is formed using a dispersion or solution containing a conductive polymer, and the moisture content in the electrolyte is set to 6.0 mass % or less, thereby preventing a decrease in adhesion between the cathode foil and the conductive layer, and between the anode foil or the conductive layer and the conductive polymer layer, and thus preventing an increase in ESR while maintaining a high capacity.

[0052] If the moisture content in the electrolyte is less than 0.1% by mass, the dielectric layer is poorly restored, and leakage current cannot be suppressed. If the moisture content exceeds 6.0% by mass, ESR increases. Thus, in this embodiment, it is important to set the moisture content in the electrolyte to 0.1% by mass or more and 6.0% by mass or less. From the viewpoint of further reducing the ESR, the moisture content in the electrolyte is preferably 5.0% by mass or less. From the viewpoint of further reducing the leakage current, the moisture content in the electrolyte is preferably 0.5% by mass or more, and more preferably 1.0% by mass or more. These lower and upper limits can be combined arbitrarily. The moisture content in the electrolyte may be, for example, 0.1 to 5.0% by mass or 0.5 to 5.0% by mass.

[0053] The moisture in the electrolytic solution does not necessarily have to be contained in the electrolytic solution used when assembling the electrolytic capacitor, and may be mixed into the electrolytic solution during the process of assembling the electrolytic capacitor. For example, the moisture may be contained in the components of the electrolytic capacitor beforehand, or may be contained in a dispersion or solution containing a conductive polymer.

[0054] The electrolyte is not particularly limited as long as it has the above-mentioned water content, and a non-aqueous solvent may be used, or a solution containing a non-aqueous solvent and an ionic substance (solute) dissolved in the non-aqueous solvent may be used. Note that the non-aqueous solvent is a general term for liquids other than water and liquids containing water, and includes organic solvents and ionic liquids.

[0055] Examples of the non-aqueous solvent contained in the electrolytic solution include polyols (alkylene glycols such as ethylene glycol and propylene glycol; polyalkylene glycols such as polyethylene glycol; glycerins such as glycerin and polyglycerin), cyclic sulfones such as sulfolane, lactones such as γ-butyrolactone (γBL), amides such as N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone, esters such as methyl acetate, ethers such as 1,4-dioxane, ketones such as methyl ethyl ketone, and formaldehyde. The non-aqueous solvents may be used alone or in combination of two or more.

[0056] The electrolytic solution preferably contains at least a solvent (first solvent) among the nonaqueous solvents that has no boiling point or has a high boiling point (for example, 180° C. or higher). When the electrolytic solution contains the first solvent, depletion of the electrolytic solution can be suppressed even when the electrolytic capacitor is used for a long period of time, so that high reliability can be ensured for a long period of time.

[0057] The boiling point of the first solvent may be 180° C. or higher, and may be 200° C. or higher. As the first solvent, polyol is preferable. Although polyethylene glycol, polyglycerin, and the like may not have a boiling point depending on the molecular weight, such compounds (but are liquid) are also preferable as the first solvent.

[0058] The first solvent is not necessarily contained in the electrolytic solution used when assembling the electrolytic capacitor, but may be contained in the treatment solution used in the process of assembling the electrolytic capacitor. For example, a dispersion or solution containing a conductive polymer may contain the first solvent. The first solvent has no boiling point or a high boiling point, and therefore remains in the assembled electrolytic capacitor. The remaining first solvent seeps into the electrolytic solution contained in the electrolytic capacitor, so that the electrolytic solution in the electrolytic capacitor contains the first solvent. From the viewpoint of easily ensuring the adhesion between the conductive polymer layer and the conductive layer, the amount of the first solvent contained in the dispersion is preferably 50% by mass or less of the dispersion or solution.

[0059] The amount of the first solvent contained in the electrolytic solution is preferably 3 to 90% by mass. When the amount of the first solvent is within this range, the deterioration of the adhesion between the conductive polymer layer and the conductive layer is suppressed, and the repair function of the dielectric layer can be further improved.

[0060] The solute contained in the electrolytic solution may be a salt of an anion or a cation, and preferably an organic salt in which at least one of the anion and the cation is an organic substance. Examples of the organic salt include trimethylamine maleate, triethylamine borodisalicylate, ethyldimethylamine phthalate, mono-1,2,3,4-tetramethylimidazolinium phthalate, and mono-1,3-dimethyl-2-ethylimidazolinium phthalate. The solute may be used alone or in combination of two or more kinds. <Manufacturing method of electrolytic capacitors> Hereinafter, an example of a method for manufacturing an electrolytic capacitor according to an embodiment of the present invention will be described step by step.

[0061] The electrolytic capacitor can be obtained through the steps of preparing a dispersion or solution (first treatment liquid) containing a conductive polymer (first step), preparing an anode foil with a dielectric layer (second step), preparing a cathode foil with a conductive layer (third step), impregnating the anode foil, cathode foil, and a separator interposed between the anode foil and cathode foil as necessary with the first treatment liquid to obtain a capacitor element (fourth step), and impregnating the capacitor element with an electrolytic solution (fifth step). Through the fourth step, a conductive polymer layer can be formed. The solvent component may be removed at an appropriate stage. (i) First step In the first step, a first processing liquid containing a conductive polymer (and a dopant) and a solvent (second solvent) is prepared.

[0062] The first treatment liquid can be obtained, for example, by dispersing or dissolving the conductive polymer (and the dopant) in the second solvent. The first treatment liquid can also be obtained, for example, by polymerizing the raw material of the conductive polymer (for example, a precursor such as a monomer and / or oligomer of the conductive polymer) in the presence of the dopant in the second solvent. When preparing the first treatment liquid by polymerization, unreacted raw materials and by-products may be removed as necessary. Alternatively, after polymerization is performed using a part of the second solvent, the remainder of the second solvent may be added to the obtained mixture.

[0063] The second solvent is not particularly limited and may be water or a non-aqueous solvent (organic solvent, ionic liquid, etc.). Among them, the second solvent is preferably a polar solvent. The polar solvent may be a protic solvent or an aprotic solvent.

[0064] Examples of protic solvents include monohydric alcohols (methanol, ethanol, propanol, butanol, etc.), polyols (alkylene glycols such as ethylene glycol and propylene glycol; polyalkylene glycols such as polyethylene glycol; glycerins such as glycerin and polyglycerin, etc.), glycol monoethers such as diethylene glycol monobutyl ether, formaldehyde, and water.

[0065] Examples of aprotic solvents include amides such as N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone, esters such as methyl acetate, ketones such as methyl ethyl ketone and γ-butyrolactone, ethers (e.g., cyclic ethers) such as 1,4-dioxane, sulfones such as dimethyl sulfoxide and sulfolane, and carbonate compounds (e.g., cyclic carbonates) such as propylene carbonate.

[0066] Among them, the second solvent is preferably a protic solvent. From the viewpoint of improving the handleability of the first treatment liquid and the dispersibility of the conductive polymer, it is preferable that the second solvent contains water. When the second solvent contains a polyol, the conductivity of the conductive polymer layer is easily increased (that is, the ESR is easily reduced). Therefore, it is also preferable that the second solvent contains a polyol, and it is also preferable to use a second solvent containing at least water and a polyol.

[0067] The first treatment liquid is preferably a dispersion in which the conductive polymer (and dopant) is dispersed in the second solvent. In the dispersion, the conductive polymer and / or dopant are preferably in the form of particles (or powder). The average particle size of the particles dispersed in the dispersion is preferably 5 to 100 nm. The average particle size can be determined, for example, from the particle size distribution by dynamic light scattering.

[0068] The amount of the dopant contained in the first treatment liquid is preferably 10 to 1000 parts by mass, and more preferably 50 to 200 parts by mass, relative to 100 parts by mass of the conductive polymer.

[0069] The concentration of the conductive polymer (including a dopant or a polyanion) in the first treatment liquid is preferably, for example, 0.5 to 3 mass %. The first treatment liquid of such a concentration is suitable for depositing an appropriate amount of the conductive polymer and is easy to be impregnated, which is advantageous in terms of improving productivity.

[0070] The first treatment liquid may contain known additives, etc., as necessary. (ii) Second step In the second step, as described above, the surface of the anode foil is subjected to, for example, chemical conversion treatment to form a dielectric layer on the surface of the anode foil. (iii) Third step In the third step, a cathode foil having a conductive layer including a carbon layer formed on the surface is prepared. More specifically, for example, the conductive layer can be formed by forming a carbon layer including conductive carbon on the cathode foil.

[0071] The carbon layer may be formed by adhering powdered conductive carbon to the surface of the cathode foil, or by applying a mixture (e.g., a slurry) containing conductive carbon and a binder to the surface of the cathode foil to form a coating film and drying the coating film, or by heat-treating the coating film to remove the binder.

[0072] The conductive layer including the carbon layer is preferably formed by depositing conductive carbon on the surface of the cathode foil using a gas phase method, such as chemical vapor deposition, vacuum deposition, sputtering, or ion plating.

[0073] In the third step, if necessary, a base layer may be formed on the surface of the cathode foil, and a carbon layer may be formed on the base layer as described above to form a conductive layer. The base layer constituting the conductive layer may be formed in the same manner as the carbon layer, using a non-carbonaceous conductive inorganic material. The base layer is preferably formed by depositing a non-carbonaceous conductive inorganic material on the surface of the cathode foil using a vapor phase method. (iv) 4th step In the fourth step, the anode foil on which the dielectric layer is formed, the cathode foil on which the conductive layer is formed, and the separator as necessary are impregnated with the first treatment liquid. More specifically, in the fourth step, the anode foil on which the dielectric layer is formed and the cathode foil on which the conductive layer is formed are wound with a separator interposed therebetween, and the first treatment liquid may be impregnated into a wound body. The impregnation with the first treatment liquid may be performed by immersing the wound body in the first treatment liquid, or by injecting the first treatment liquid into the wound body.

[0074] The impregnation with the first treatment liquid may be performed under atmospheric pressure, or under reduced pressure, for example, 10 to 100 kPa, preferably 40 to 100 kPa. The impregnation may be performed under ultrasonic vibration, if necessary. The impregnation time depends on the size of the capacitor element 10, but is, for example, 1 second to 5 hours, preferably 1 minute to 30 minutes.

[0075] After the anode foil and the cathode foil (and the separator) are impregnated with the first treatment solution, they may be dried as necessary. At least a part of the second solvent is removed by drying. Drying may be performed under heating, and may be performed under reduced pressure as necessary.

[0076] In this manner, through the fourth step, a conductive polymer layer is formed between the anode foil and the cathode foil, thereby forming capacitor element 10. (v) Fifth step In the fifth step, the capacitor element obtained in the fourth step is impregnated with an electrolyte.

[0077] Impregnation of the electrolyte into the capacitor element 10 is not particularly limited and can be performed by a known method. For example, the capacitor element 10 may be immersed in the electrolyte, or the electrolyte may be poured into a container containing the capacitor element 10. The impregnation of the electrolyte into the capacitor element 10 may be performed under reduced pressure (for example, 10 to 100 kPa) as necessary.

[0078] It is preferable to appropriately adjust the water content of the electrolyte used so that the water content of the electrolyte after assembly of the electrolytic capacitor falls within the above range. (others) Capacitor element 10 may be sealed. More specifically, capacitor element 10 is first housed in bottomed case 11 such that lead wires 14A and 14B are located on the open upper surface of bottomed case 11. The material of bottomed case 11 may be a metal such as aluminum, stainless steel, copper, iron, brass, or an alloy of these metals.

[0079] Next, sealing member 12, which is formed so that lead wires 14A and 14B pass through it, is placed above capacitor element 10, and capacitor element 10 is sealed within bottomed case 11. Sealing member 12 may be made of an insulating material. As the insulating material, an elastic body is preferable, and among them, silicone rubber, fluororubber, ethylene propylene rubber, chlorosulfonated polyethylene rubber (such as Hypalon rubber), butyl rubber, isoprene rubber, and the like, which have high heat resistance, are preferable.

[0080] Next, a horizontal drawing process is performed near the open end of bottomed case 11, and the open end is curled by crimping it to sealing member 12. Then, seat plate 13 is placed on the curled portion to complete the electrolytic capacitor as shown in Fig. 1. After that, an aging process may be performed while applying the rated voltage.

[0081] In the above embodiment, a wound-type electrolytic capacitor has been described, but the scope of application of the present invention is not limited to the above, and the present invention can also be applied to other electrolytic capacitors, such as a chip-type electrolytic capacitor that uses a metal sintered body instead of an anode foil, or a laminate-type electrolytic capacitor that uses a metal plate instead of an anode foil. EXAMPLES

[0082] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples. Example 1 Using the procedure below, a wound-type electrolytic capacitor with a rated voltage of 35 V and a rated capacitance of 47 μF, as shown in Figure 1, was fabricated and evaluated. (1) Manufacturing of electrolytic capacitors (Preparation of anode foil with dielectric layer) An aluminum foil having a thickness of 100 μm was subjected to an etching treatment to roughen the surface of the aluminum foil, and then a dielectric layer was formed on the surface of the aluminum foil by a chemical conversion treatment using an aqueous solution of ammonium adipate, thereby preparing an anode foil having a dielectric layer.

[0083] (Preparation of cathode foil with conductive layer) A cathode foil was prepared by forming a conductive layer on the surface of an aluminum foil having a thickness of 30 μm by ion plating of conductive carbon. The conductive layer had a thickness of 3 nm.

[0084] (Making of the roll) Anode lead tabs and cathode lead tabs were connected to the anode foil and cathode foil, and the anode foil and cathode foil were wound with a separator interposed therebetween while the lead tabs were rolled up to obtain a wound body. An anode lead wire and a cathode lead wire were connected to the ends of the lead tabs protruding from the wound body, respectively. The wound body was then subjected to a chemical conversion treatment again to form a dielectric layer on the cut ends of the anode foil. Next, the ends of the outer surface of the wound body were fixed with a winding stop tape.

[0085] (Preparation of first treatment liquid) A mixed solution was prepared by dissolving 3,4-ethylenedioxythiophene and polystyrenesulfonic acid as a dopant in ion-exchanged water. While stirring the obtained solution, ferric sulfate and sodium persulfate (oxidizing agent) dissolved in ion-exchanged water were added to carry out a polymerization reaction. After the reaction, the obtained reaction solution was dialyzed to remove unreacted monomers and excess oxidizing agent, and a dispersion containing poly3,4-ethylenedioxythiophene doped with polystyrenesulfonic acid (PEDOT-PSS) was obtained. The concentration of PEDOT-PSS in the dispersion was about 2 mass%, and the mass ratio of PSS to PEDOT (=PSS:PEDOT) was about 2:1. A first treatment liquid in the form of a dispersion was prepared by adding 5 mass% ethylene glycol (second solvent) to the obtained dispersion and stirring it.

[0086] (Impregnation of first treatment liquid) The wound body was impregnated with the first treatment solution for 5 minutes. The wound body was then heated at 150° C. for 20 minutes to remove the solvent. In this manner, a capacitor element was produced in which a conductive polymer layer was formed between the anode foil and the cathode foil. (Electrolyte Impregnation) The capacitor element was then impregnated with an electrolyte under reduced pressure. A solution containing γBL:glycerin:mono(ethyldimethylamine)phthalate (solute) = 50:25:25 (mass ratio) was used as the electrolyte. The amount of moisture contained in the γBL and glycerin used was measured in advance, and the amount of moisture in the electrolyte was adjusted by adding water to the electrolyte or evaporating the moisture by heating so that the amount of moisture in the electrolyte reached the desired amount. In the electrolyte, γBL and glycerin were the first solvents. (Sealing of capacitor elements) The capacitor element impregnated with the electrolytic solution was housed in an exterior case as shown in Figure 1 and sealed to produce an electrolytic capacitor. A total of 300 electrolytic capacitors were produced in the same manner. (2) Evaluation The following evaluations were performed on 120 randomly selected electrolytic capacitors, and the average values ​​were calculated. (a) Moisture content The electrolyte was removed from the assembled electrolytic capacitor, and the moisture content (mass %) in the electrolyte was measured by the Karl Fischer method, which revealed that the moisture content in the electrolyte was 0.10 mass %. (b) Amount of the first solvent in the electrolyte The electrolytic solution was extracted from the electrolytic capacitor, and the amount (mass %) of the first solvent contained in the electrolytic solution was measured by gas chromatography, which revealed that the amount of the first solvent in the electrolytic solution was 75.0 mass %. (c) Capacitance and ESR value The initial characteristics of the electrolytic capacitor were measured: capacitance (μF) and ESR value (mΩ). Specifically, the initial capacitance (μF) of the electrolytic capacitor was measured at a frequency of 120 Hz using an LCR meter for four-terminal measurement. In addition, the ESR value (mΩ) of the electrolytic capacitor was measured at a frequency of 100 kHz using an LCR meter for four-terminal measurement.

[0087] The capacitance (μF) and ESR value (mΩ) after a high-temperature storage test at 125° C. for 4000 hours were also measured in the same manner as for the initial characteristics described above.

[0088] The capacitance and ESR values ​​were each measured for 120 randomly selected electrolytic capacitors, and the average values ​​were calculated. (d) Leakage current (LC) As the initial characteristics of the electrolytic capacitor, the rated voltage was applied to the electrolytic capacitor and the leakage current (μA) was measured after 2 minutes.

[0089] The leakage current (μA) after a high-temperature storage test at 125° C. for 4000 hours was also measured in the same manner as in the case of the initial characteristics described above. Examples 2 to 6 and Comparative Examples 1 to 2 An electrolytic capacitor was produced and evaluated in the same manner as in Example 1, except that the amount of water in the electrolyte solution of the assembled electrolytic capacitor was adjusted to the value shown in Table 1. The amount of the first solvent in the electrolyte solution of the assembled electrolytic capacitor was as follows.

[0090] Example 2: 76.0% by weight Example 3: 75.8% by weight Example 4: 75.6% by weight Example 5: 75.7% by weight Example 6: 75.6% by weight Comparative example 1: 75.8% by mass Comparative example 2: 75.1% by mass Comparative Example 3 A solution was prepared by mixing 1 part by mass of 3,4-ethylenedioxythiophene as a polymerizable monomer, 2 parts by mass of ferric p-toluenesulfonate as an oxidizing agent and dopant component, and 4 parts by mass of n-butanol as a solvent. A wound body prepared in the same manner as in Example 1 was immersed in the obtained solution, pulled out, and then left at 85°C for 60 minutes to prepare a capacitor element in which a conductive polymer layer was formed between the anode foil and the cathode foil. An electrolytic capacitor was prepared and evaluated in the same manner as in Example 3, except that the obtained capacitor element was used.

[0091] The amount of the first solvent in the electrolytic solution of the electrolytic capacitor was 74.4 mass %. Comparative Example 4 In Comparative Example 4, an electrolytic capacitor was produced and evaluated in the same manner as in Example 3, except that no conductive layer was formed on the surface of the aluminum foil. Comparative Example 5 In Comparative Example 5, a solid electrolytic capacitor was produced without using an electrolytic solution. More specifically, a capacitor element was produced in which a conductive polymer layer was formed between an anode foil and a cathode foil in the same manner as in Example 1. The resulting capacitor element was housed in an exterior case and sealed to produce a solid electrolytic capacitor, which was evaluated in the same manner as in Example 1.

[0092] The results of the examples and comparative examples are shown in Table 1. Examples 1 to 6 are A1 to A6, and Comparative Examples 1 to 5 are B1 to B5.

[0093] [Table 1]

[0094] As shown in Table 1, in the examples, high capacity was obtained both initially and after 4000 hours of exposure to high temperature, and the initial ESR and leakage current were also suppressed to be low. In Comparative Example 1, in which the moisture content of the electrolyte was 0.05 mass%, the dielectric layer was not sufficiently repaired, and the leakage current after exposure to high temperature increased significantly. In Comparative Example 2, in which the moisture content of the electrolyte was 8.00 mass%, and Comparative Example 3, in which the conductive polymer layer was formed by polymerization, the ESR after exposure to high temperature was significantly higher than in the examples. In Comparative Example 4, which did not have a conductive layer, the initial capacity was lower than in the examples. In Comparative Example 5, which was a solid electrolytic capacitor, the leakage current after exposure to 4000 hours increased. [Industrial Applicability]

[0095] The present invention can be used in an electrolytic capacitor including a capacitor element having a conductive polymer layer and an electrolyte. [Explanation of symbols]

[0096] 10: capacitor element, 11: bottomed case, 12: sealing member, 13: seat plate, 14A, 14B: lead wires, 15A, 15B: lead tabs, 21: anode foil, 22: cathode foil, 23: separator, 24: winding stop tape

Claims

1. The capacitor element and the electrolyte are provided. The capacitor element is an anode foil having a dielectric layer formed thereon; a cathode foil facing the anode foil and having a layer containing conductive carbon formed on a surface thereof; a conductive polymer layer interposed between the anode foil and the cathode foil and including a conductive polymer; The electrolyte solution includes a first solvent, The first solvent has no boiling point or has a boiling point of 180° C. or higher; the conductive polymer layer is formed using a dispersion or a solution containing the conductive polymer, the conductive polymer layer is in contact with the layer containing conductive carbon, The electrolytic capacitor has an electrolytic solution having a water content of 0.1 to 6.0% by mass.

2. An electrolytic capacitor as described in claim 1, wherein the conductive polymer layer is in contact with conductive carbon contained in the layer containing conductive carbon.

3. An electrolytic capacitor as described in claim 1 or 2, wherein the first solvent includes a polyol.

4. The electrolytic capacitor described in claim 3, wherein the polyol includes a glycerin.

5. An electrolytic capacitor described in any one of claims 1 to 4, wherein the amount of the first solvent contained in the electrolyte solution is 3 to 90 mass %.

6. An electrolytic capacitor according to claim 1, wherein the layer containing the conductive carbon further contains at least one metal selected from titanium and nickel or a compound of said metal.

Citation Information

Patent Citations

  • Solid-state electrolytic capacitor

    JP1998270291A

  • Electrolytic capacitor and manufacture thereof

    JP2000182898A

  • Solid electrolytic capacitor electrode member, its manufacturing method and solid electrolytic capacitor using solid electrolytic capacitor electrode member

    JP2006100478A

  • Electrolyte capacitor and manufacturing method thereof

    JP2006190878A

  • Electrolytic-capacitor and manufacturing method therefor

    JP2008010657A